Hubungan Pengetahuan dan Persepsi Harga dengan Penggunaan Pestisida dalam Usahatani - Anas Affandi; Aldon Sinaga; Ana Arifatus S (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2014)
The use of pesticides for certain crops can not be avoided because of the character of the plant, one of which is coffee. Pesticides in the cultivation of coffee is often used unwisely, excessive doses and the use of an incorrect type, the effect is potentially decreasing the quality of the coffee. As the times and the changing mindset of consumers about organic farming encourage to consume organic coffee products. This is evidenced by the increasing demand than available supply. The aim of this study are: 1) Knowing the main source of information used by farmers in the purchase decision and the use of pesticides in the cultivation of coffee; 2) Determine the relationship of knowledge to the purchase decision and the use of pesticides in the cultivation of coffee; 3) Knowing the relationship of knowledge to the effectiveness of the use of pesticides in the cultivation of coffee. The study was conducted in the village Sumber Tempur Wonosari Subdistrict precisely in farmer groups Sumber Makmur I census method against 30 members of farmer groups. The results showed that 1) The source of information is important in decision making pesticide use in coffee farming is a row; Reference Group, Recommendations other institutions, consumer preferences, and family references; 2) Correlation analysis showed that the knowledge of the specifications of pesticides (0.72), knowledge threshold HPT attack (0.60) is strongly correlated with the complexity of the use of pesticides; 3) Correlation analysis showed that the knowledge of the specifications of pesticides (0.69), knowledge threshold HPT attack (0.76) is strongly correlated with the effectiveness of the use of pesticides.